IDENTIFICATION OF CANCER AWARENESS AMONG ADULTS AFTER GIVEN CANCER EDUCATION APP (PEKA) IN JEMBER, INDONESIA - Martiana, Ina; Hendra Dwi Cahyono (Journal of Innovation Research and Knowledge, 2025)
One of the main barriers to cancer prevention and early detection is the general lack of awareness of cancer risk factors, symptoms, and screening options. Improving long-term cancer outcomes requires increasing public knowledge through interesting strategies with mobile app called PEKA. This study aims to identify cancer awareness among adults by given education mobile-app. This study used a quantitative descriptive method with 75 respondents. Descriptive analysis of the data was utilized to compile awareness and demographic traits. The result shows mostly 39,7% was answer incorrectly about cancer warning sign, 52% doesn’t know the screening programme, and the descriptive response displays a variety of responses. The results emphasize the benefits of multimodal, community-integrated teaching strategies, especially for individuals with poor computer literacy or educational achievement. PEKA and other mobile apps should be considered complementary tools rather than standalone solutions.